Thyristor Controlled Series Compensator based Optimal Reallocation of Generators for Contingency Management - Kumar, B. Sravana; Suryakalavathi, M.; Kumar, G.V.Nagesh (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
Privatization of the power industry has made proper utilization of the available resources a compulsory requirement. Optimal power flow (OPF) is an ideal solution to the problem. At the same time, stable operation of the power systems in both normal and contingency condition is of vital importance. Use of FACTS devices is a good method to stop further contingencies in the power system. In this paper, a combined index based strategy for the optimal placement of Thyristor Controlled Series Compensator (TCSC) and optimal tuning of generators using Krill Herd Algorithm has been proposed for contingency management. The contingency analysis has been done using a new method, namely, rapid contingency ranking technique (RCRT). The TCSC has been placed on the basis of an index which is a combination of Line Utilization Factor (LUF) and Fast Voltage Stability Index (FVSI). A multi-objective function has been chosen for tuning the generators. The multi-objective function includes voltage deviation, active power generation cost and transmission line loss. The proposed method has been tested and implemented on an IEEE 30 bus system. Privatization of the power industry has made proper utilization of the available resources a compulsory requirement. Optimal power flow (OPF) is an ideal solution to the problem. At the same time, stable operation of the power systems in both normal and contingency condition is of vital importance. Use of FACTS devices is a good method to stop further contingencies in the power system. In this paper, a combined index based strategy for the optimal placement of Thyristor Controlled Series Compensator (TCSC) and optimal tuning of generators using Krill Herd Algorithm has been proposed for contingency management. The contingency analysis has been done using a new method, namely, rapid contingency ranking technique (RCRT). The TCSC has been placed on the basis of an index which is a combination of Line Utilization Factor (LUF) and Fast Voltage Stability Index (FVSI). A multi objective function has been chosen for tuning the generators. The multi-objective function includes voltage deviation, active power generation cost and transmission line loss. The proposed method has been tested and implemented on an IEEE 30 bus system.